Miniature Microwave Sensor for Detecting Vital Sign under Low Frequency Motion of Human Subject - Yun, Gi-Ho; ., . (International Journal of Engineering and Technology, 2018)
In this paper, we propose a microwave sensor circuit that can detect vital sign close to human chest. It operates as a sensor in low frequency movement of human subjects, and circuitry is constructed to realize small size and low power consumption to fit wearable device. A self-oscillating detector and a feedback circuit were connected to the planar microstrip patch radiator designed at 2.4 GHz ISM band. The feedback circuit controls the oscillation frequency which changes in proportion to the movement, thereby stably detecting the heart rate signal through the nonlinear characteristic of the self-oscillating detector. The boards that implement the patch radiator and the circuit board where the active circuits are placed, share the ground plane. Owing to the miniaturized circuit architecture, the sensor consumes only about 20mA current at 5V DC voltage. Besides, measurement results confirm that the proposed sensor can detect the vital sign of the human subject moving with a low frequency within 40 mm from the sensor.Â Â